Maternal Mortality in a Tertiary Care Hospital: A Five Year Review - RizwanaAnjum ,MalihaSadaf,SobiaNawaz (Journal of Rawalpindi Medical College, 2018)
Background: To find out the maternal mortality in a tertiary care hospital. Methods: In this retrospective study, data regarding maternal mortality was collected . Information recorded was age, parity, booking and literacy status, socio-economic status, cause of death and total stay in the hospital. Total number of live births was also calculated for the same time period.Maternal mortality rate for the study period was calculated. Results:A total of 79 maternal deaths were noted out of 39704 live births. Age group 26–35 years showed higher number of maternal deaths, while in multiparous women and un-booked patients almost equal number of deaths were observed. Most were due to direct causes (70.88%), where as 29.11% were due to indirect causes. The leading direct causes of maternal mortality were obstetric hemorrhage in39.24% (n = 31), Eclampsia in 15.18% (n = 12)and puerperal sepsis in 8.86% (n =07). Among indirect causes, embolism accounted for 12.65%. Out of these, 03 cases resulted from Amniotic fluid embolism while rest of the 07 were due to pulmonary embolism. Conclusion: Being a tertiary care hospital, our institute receives large number of complicated referred cases from neighbouring towns resulting in relatively high maternal mortality rate..On the other hand,most of the observed deaths were preventable, so there is a wide scope for improvement.